2014
DOI: 10.1210/en.2013-1816
|View full text |Cite
|
Sign up to set email alerts
|

Eugen Steinach: The First Neuroendocrinologist

Abstract: In 1936, Eugen Steinach and colleagues published a work that brought steroid biochemistry to the study of sexual behavior and, using synthetic androgens and estrogens, foreshadowed by an astonishing 4 decades the discovery of the central role of estrogen in the sexual behavior of male rats. We offer an English translation of that paper, accompanied by historical commentary that presents Steinach as a pioneer in reproductive neuroendocrinology. His work 1) established the interstitial cells as the main source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…In the second study, Steinach et al (1936; Södersten et al, 2014) first showed that injection of EB, but not androgens, replicated the effect of testicular extracts on cerebral blood flow, an assay of an effect on the brain. It was then hypothesized that estrogen also acts on the brain to stimulate sexual behavior by synergizing with androgens, as had been demonstrated in the seminal vesicles (Freud, 1933).…”
Section: Discovery Of the Effects Of Estrogen In Male Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second study, Steinach et al (1936; Södersten et al, 2014) first showed that injection of EB, but not androgens, replicated the effect of testicular extracts on cerebral blood flow, an assay of an effect on the brain. It was then hypothesized that estrogen also acts on the brain to stimulate sexual behavior by synergizing with androgens, as had been demonstrated in the seminal vesicles (Freud, 1933).…”
Section: Discovery Of the Effects Of Estrogen In Male Ratsmentioning
confidence: 99%
“…However, the idea was launched 34 years earlier in a report by Steinach et al (1936; translated in Södersten et al, 2014), which was not mentioned when the effect of estrogen was rediscovered in the early 1970s (Södersten, 2012). Thus, the original article (Steinach et al, 1936), which demonstrated that a behaviorally ineffective dose of estradiol benzoate (EB) synergizes with a likewise behaviorally ineffective dose of testosterone in restoring ejaculation in castrated rats hibernated for a long time, although it was reviewed in detail in 1938 when Steinach was nominated for the seventh time for the Nobel Prize (Liljestrand, 1938).…”
Section: Introductionmentioning
confidence: 99%
“…At the gonadal level, for example, Marshall and Jolly described the effects of spaying pregnant rats as early as 1905, 19 and used these results as well as others to postulate that the ovary released two distinct hormones, later called oestrin/estrin (or estrogen) and progestin (or progesterone), which had different functions (recapitulated in Marshall's Croonian Lecture, 1936 20 ). 22). 21; retold in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Steinach, who was nominated for the Nobel Prize five times, became world-famous for his hormone therapies and his anti-aging operation, which Sigmund Freud, among others, underwent. «To be steinached» was a common expression in the 1920s and became so well-known even in English that newspapers in the USA used it without further explanation (Logan, 2013;Södersten, Crews, Logan, & Soukup, 2013;Walch, 2016).…”
Section: Scientistsmentioning
confidence: 99%